Left atrial appendage occlusion using LAmbre Amulet and Watchman in atrial fibrillation. Issue 4 (April 2019) - Chen, Shaojie; Chun, K.R. Julian; Bordignon, Stefano; Weise, Felix K.; Nagase, Takahiko; Perrotta, Laura; Bologna, Fabrizio; Schmidt, Boris
Highlights: This registry supports the favorable outcomes of three devices in left atrial appendage (LAA) occlusion. The three devices exhibit good peri-procedural performance and follow-up. The LAmbre may be particularly for patients with complicated LAA anatomy. Abstract: Background: Left atrial appendage closure (LAAC) has been suggested as an alternative to anticoagulation in non-valvular atrial fibrillation (AF). The present study aimed to compare a LAmbre LAA occluder system [Lifetech Scientific (Shenzhen) Co. Ltd., Shenzhen, China] with the most investigated Amulet (St. Jude Medical Inc., St. Paul, MN, USA) and Watchman (Boston Scientific, Plymouth, MN, USA) devices in terms of peri-procedural and short-term outcomes. Methods: This is a prospective observational study. Results: Overall, 140 patients (50 female, mean age 76.2 ± 8.4 years) were consecutively enrolled. Mean CHA2DS2-VASc score was 3.8 ± 1.5, and mean HAS-BLED score was 3.9 ± 1.1. Baseline clinical characteristics were comparable between the three groups (LAmbre, n  = 30; Amulet, n  = 74; Watchman, n  = 36); the LAmbre group had significantly more patients with complicated LAA morphology ( p  = 0.006). The implant success rate was 100% in LAmbre, 99% in Amulet, and 100% in Watchman group ( p  = 0.638). The number of device repositions was not significantly different between groups (0.7 ± 1.1 in LAmbre, 1.0 ± 2.0 in Amulet, and 1.4 ± 1.8 in Watchman group, p  = 0.345). Fluoroscopic and procedural times were similar between groups. Major peri-procedural adverse events did not differ between groups (0% vs. 0% vs. 2.8%, p  = 0.233). Six months' follow-up showed good device stability and patients' clinical condition in all groups. Conclusion: LAmbre, Amulet, and Watchman exhibit remarkable implant success rate, low risk of peri-procedural adverse events, and good clinical outcomes.